TEACHER PERFORMANCE REVIEWING FROM AUTONOMY, WORKLOAD AND JOB SATISFACTION THROUGH BALANCE OF LIFE AND WORK AS MEDIATION IN PRIVATE SCHOOL - Chumaira Amalia Fadhilah; Bambang Mursito; Ida Aryati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to determine the effect of the variables of autonomy, workload and job satisfaction on teacher performance through work-life balance in private schools.The research method uses a quantitative research design. In this study the population taken is the performance of teachers. Based on the information obtained, the total population is 63 respondents. The sample used was 63 respondents who came from a population called the saturated sample. The sampling technique used in this study is a saturated sampling technique. The data analysis technique used is the Partial Least Square (PLS) test. The results showed that the variables of autonomy, workload, and job satisfaction had a positive and significant effect on teacher performance through work-life balance. The results showed that the work-life balance variable had a negative and significant effect on teacher performance. Suggestions from this research, private schools must continue to increase the autonomy, workload, and job satisfaction that exist in the teacher through a balance of life and work, so that the teacher's performance will increase and be better than before. Keywords: Teacher Performance, Autonomy, Workload, Job Satisfaction, Work and Life Balance